Assistance for Registration of Halal Certification to MSMEs Products in Banten Province - Fitria Riany Eris; Nurul Annazhifah; Zulfatun Najah; Puji Wulandari; Tubagus Bahtiar Rusbana (EQUATOR SINAR AKADEMIA, 2023)
Consumer’s awareness of the importance of halal products has increased in Indonesia. However, there are still many producers in Indonesia, especially MSMEs in Banten province who have not applied for halal certification due to the lack of their knowledge about the urgency of halal certification, and the process for obtaining halal certificate which are considered difficult. This service activity involved selected MSMEs in Banten province and the academist at Department of Food Technology, Sultan Ageng Tirtayasa University, in order to provide a good understanding of the benefits of halal certification and assist them during registration process until they get halal certificate for their products. This carried out in 3 stages, there were lectures and discussion about the process of halal certification, preparation of halal manuals, and halal registration. The results of this activity were the issuance of halal certificates for 8 selected MSMEs in Banten province which are valid for the next 4 years.